Roles of zirconia-doping in the sintering process of high quality Tb3Al5O12 magneto-optic ceramics. (February 2020) - Chen, Jie; Tang, Yanru; Chen, Chong; Hao, Deming; Yi, Xuezhuan; Ao, Gang; Tian, Yanna; Zhou, Shengming
Abstract: In this work, the effect of ZrO2 -doping on the microstructure evolution and phase change of Tb3 Al5 O12 (TAG) ceramics has been investigated systematically. Except for the transformation of Zr 4+ –Zr 3+, a novel phenomenon is discovered in the final stage of sintering that a second phase of ZrO2 is discharged to the surface of samples at the sintering temperature higher than 1550 °C, which is accompanied with a largely promoted grain growth at the same time. The discharge behavior is considered to contribute to the enhanced optical quality of TAG ceramics for the decreasing residual impurity in grain boundaries. Graphical abstract: Image, graphical abstract